Who's slipping through the cracks? A comprehensive individual, clinical and health system characterization of people with virological failure on first‐line HIV treatment in Uganda and South Africa. Issue 5 (9th November 2021) - Reynolds, Zahra; McCluskey, Suzanne M.; Moosa, Mahomed Yunus S.; Gilbert, Rebecca F.; Pillay, Selvan; Aturinda, Isaac; Ard, Kevin L.; Muyindike, Winnie; Musinguzi, Nicholas; Masette, Godfrey; Moodley, Pravi; Brijkumar, Jaysingh; et al.
Abstract: Objectives: HIV virological failure remains a major threat to programme success in sub‐Saharan Africa. While HIV drug resistance (HIVDR) and inadequate adherence are the main drivers of virological failure, the individual, clinical and health system characteristics that lead to poor outcomes are not well understood. The objective of this paper is to identify those characteristics among people failing first‐line antiretroviral therapy (ART). Methods: We enrolled a cohort of adults in HIV care experiencing virological failure on first‐line ART at five sites and used standard statistical methods to characterize them with a focus on three domains: individual/demographic, clinical, and health system, and compared each by country of enrolment. Results: Of 840 participants, 51% were women, the median duration on ART was 3.2 years [interquartile range (IQR) 1.1, 6.4 years] and the median CD4 cell count prior to failure was 281 cells/µL (IQR 121, 457 cells/µL). More than half of participants [53%; 95% confidence interval (CI) 49–56%] stated that they had > 90% adherence and 75% (95% CI 72–77%) took their ART on time all or most of the time. Conversely, the vast majority (90%; 95% CI 86–92%) with a completed genotypic drug resistance test had any HIV drug resistance. This population had high health system use, reporting a median of 3 (IQR 2.6) health care visits and a median of 1 (IQR 1.1) hospitalization in the preceding 6 months. Conclusions: Patients failing first‐line ART in sub‐Saharan Africa generally report high rates of adherence to ART, have extremely high rates of HIV drug resistance and utilize significant health care resources. Health systems interventions to promptly detect and manage treatment failure will be a prerequisite to establishing control of the HIV epidemic.